Carbon Neutrality, International Trade, and Agricultural Carbon Emission Performance in China - Li, Gaoya; Hou, Cuiping; Zhou, Xijun (Frontiers in Environmental Science, 2022)
Carbon neutral is an important goal towards global sustainable development and an effective means of addressing climate change. The realization of carbon neutral depends on the vigorous development of international trade among countries around the world, especially by relying on international trade to upgrade the level of technology. This paper uses the Malmquist Index, panel data regression model, and data from 2005–2020 to quantify the relationship between agricultural carbon emission performance and international trade. The results show that Agricultural Carbon Emission of China has increased slowly since 2005. In the econometric model of agricultural carbon emission performance, the coefficient of the total trade in agricultural products is 0.0444, indicating that agricultural international trade significantly promotes agricultural carbon emission performance. Suggestions on agricultural international trade and the development of low carbon agricultural production are put forward, which will provide technical support for carbon neutral.